(untitled) (Research, Society and Development, 2020)
Violence against women is a public health problem with relationships intrinsic to historical facts and cultural values. This work aims to analyze historical and cultural facts linked to the respective theme. A narrative review was carried out between the months of September and November 2020, by searching databases focused on the following sources: academic articles, monographs and books. The results found show that, throughout history, the man has imposed himself as the main figure of the facts and events, while the woman has become a figure of submission and support. It is noticeable that writing, in the Ancient Age, and the performance of the Catholic Church, in the Medieval Age, contributed strongly to enhance the male gender. In those times, women practically did not dominate writing, leaving men to literary production, which brought their perceptions among them female submission. Therefore, the feminine point of view and its possible contributions in areas neglected by men have been disadvantaged by history, and it is precisely these historical facts that created cultural values ​​in society that contributed to the increase in cases of violence against women. In view of this research, it is concluded that violence against women has historical and cultural roots, linked mainly to machismo. Despite the advances in legal laws achieved over the years, services for the protection of victimized women are worryingly ineffective. The data indicate a real need to expand and consolidate measures to protect women’s safety.